C-reactive protein and the acute phase reaction in geriatric patients: discovery, structure and function of C-reactive protein - Bertsch, Thomas; Triebel, Jakob; Bollheimer, Cornelius; Christ, Michael; Sieber, Cornel; Fassbender, Klaus; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2015)
The C-reactive protein (CRP), first described as a serum component capable of precipitating the C-polysaccharide of pneumococci, is one of the most important proteins because the serum concentration...